Influence of Microstructure and Droplet Volume on Atmospheric Pitting Corrosion of 304L Austenitic Stainless Steel - Hussein, Sarkat R.; Mohammed-Ali, Haval B. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This research investigates the atmospheric pitting corrosion behavior of 304L austenitic stainless steel subjected to MgCl2 droplets, emphasizing the effects of microstructure and droplet volume. X-ray diffraction and scanning electron microscopy (SEM) show that both austenite and ferrite are present, and it is observed that the ferrite bands dissolved more in the direction the steel is rolled. SEM-energy-dispersive X-ray spectroscopy analysis identified mixed oxides and MnS inclusions. The shape of the pits changed depending on the direction of the plate: Layered pits mostly occurred on the longitudinal–transverse side, while striped pits are seen on the longitudinal–short transverse and short transverse sides, indicating variations in the material’s structure. An increase in droplet volume from 0.5 µL to 2.5 µL led to a linear rise in total pit area and a measurable increase in pit depth. These findings show that the direction of the microstructure and the size of the droplets significantly affect how likely pitting is to occur, which is important for designing and using stainless steels in environments with a lot of chloride.